Dispersion of torsional surface waves in anisotropic layer over porous half space under gravity. Issue 12 (6th September 2013) - Chattaraj, R.; Samal, S.K.; Debasis, S.
Abstract In this paper an attempt has been made to derive the frequency equation of torsional surface waves in initially stressed fiber reinforced layer lying over fluid saturated anisotropic porous half space under gravity. The dispersion equation has been obtained in terms of Whittaker function and its derivatives, which further expanded asymptotically and retain the terms upto second degree. The analysis of frequency equation bear out the pronounced effect of initial stress, transverse and longitudinal rigidity of reinforced material, gravity and porosity of the porous half space on the propagation of torsional surface waves. Moreover, it can be noted that in the absence of initial stress, reinforcement parameters, gravity and porosity, the frequency equation of torsional surface waves reduces to dispersion equation of Love waves in isotropic layer. This ensures the classical result that torsional surface waves do not propagate through isotropic homogeneous medium.